Molecular networks in FGF signaling : Flotillin-1 and Cbl-associated protein compete for the binding to fibroblast growth factor receptor substrate 2 - Tomasovic, Ana; Traub, Stephanie; Tikkanen, Ritva; Justus Liebig University Giessen (My University, 2012)
Fibroblast growth factor receptor substrate 2 (FRS2α) is a signaling adaptor protein that regulates downstream signaling of many receptor tyrosine kinases. During signal transduction, FRS2 can be both tyrosine and threonine phosphorylated and forms signaling complexes with other adaptor proteins and tyrosine phosphatases. We have here identified flotillin-1 and the cbl-associated protein/ponsin (CAP) as novel interaction partners of FRS2. Flotillin-1 binds to the phosphotyrosine binding domain (PTB) of FRS2 and competes for the binding with the fibroblast growth factor receptor. Flotillin-1 knockdown results in increased Tyr phosphorylation of FRS2, in line with the inhibition of ERK activity in the absence of flotillin-1. CAP directly interacts with FRS2 by means of its sorbin homology (SoHo) domain, which has previously been shown to interact with flotillin-1. In addition, the third SH3 domain in CAP binds to FRS2. Due to the overlapping binding domains, CAP and flotillin-1 appear to compete for the binding to FRS2. Thus, our results reveal a novel signaling network containing FRS2, CAP and flotillin-1, whose successive interactions are most likely required to regulate receptor tyrosine kinase signaling, especially the mitogen activated protein kinase pathway.
Keywords: FGF signalling; Flotillin-1; Fibroblast growth factor receptor substrate 2 (FRS2); cbl-associated protein/ponsin (CAP); signal transduction; ddc:570